Membangun Ketahanan Terhadap Bencana: Strategi Kebijakan Global dalam Menangani Pengungsi Iklim - Ria Silviana; Hieronymus Soerjatisnanta (Jurnal Interpretasi Hukum, 2025)
Climate change has emerged as a critical global issue, resulting in significant impacts such as rising temperatures, polar ice melt, and escalating sea levels, which threaten millions of lives. According to the Intergovernmental Panel on Climate Change (IPCC), approximately 3.3 to 3.6 billion people reside in areas highly vulnerable to climate change. This has led to an increasing number of climate-induced displacements, with millions of individuals—referred to as "climate refugees"—forced to flee due to extreme weather events like floods and wildfires. However, these individuals lack formal recognition and adequate legal protection under current international frameworks. The United Nations projects that up to 21.5 million people could be displaced annually due to climate-related disasters, and urgent action is required. This study aims to analyze the critical gap by examining the status of climate refugees in the international legal framework and the necessary global policy to manage climate-induced displacement effectively to enhance disaster resilience.